Gender, Growth, and Poverty Reduction - Blackden, C. Mark (World Bank, Washington, DC, 2012)
This note focuses on the core findings, and recommendations of the 1998 status report on poverty in Sub-Saharan Africa (SSA), prepared for the Special Program for Assistance for Africa (SPA), a thematic examination of the linkages between gender, growth, and poverty reduction in SSA. Primarily focused on agriculture, and the rural sector, the report argues that one of the factors constraining growth, and poverty in SSA is gender inequality in the access to, and control of a diverse range of assets. The note reviews the determinants of growth, and the interdependence of the market, and household economies, where much of women's productive work is unrecorded, (in Kenya, about sixty percent of female activities are unaccounted for, compared with only twenty four percent of male activities). Furthermore, micro-level analyses portray a consistent picture of gender-based asset inequality, pointing at patterns of disadvantage faced by women, in accessing the basic assets, and resources required for a full participation in SSA's growth potential. In education, although girls have made rapid strides in completing primary education, lowering the gender gap, differentials persist due to social, and cultural factors; and, in health, an enormous gender differential in the region's sexual, and reproductive burden of disease, is observed, as measured by deaths, and disability-adjusted life years. Recommendations include women's budget initiatives, sustained investments in education/health, and, raising the visibility of domestic work in national statistics.